2006
DOI: 10.1007/bf02893432
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneously ruptured uterine angioleiomyoma

Abstract: Angioleiomyoma is an uncommon type of leiomyoma of the uterus that originates from smooth muscle cells and contains thick-walled vessels. A 45-year-old woman with the complaint of lower abdominal pain was admitted to the hospital. In the operation a ruptured, bleeding uterine tumor was seen. She underwent total hysterectomy and bilateral salpingo-oophorectomy. On pathologic examination of the specimen, the tumor was diagnosed as angioleiomyoma. Here, an unusual clinical presentation of uterine angioleiomyoma w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
50
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(55 citation statements)
references
References 6 publications
1
50
0
4
Order By: Relevance
“…It is exceedingly rare for this tumor to be found in a location other than the lower extremities. From 1966 to 2007, only 11 cases of uterine angioleiomyoma were reported in the current English literature (Cobellis et al, 2007;Culhaci et al, 2006;Hakverdi et al, 2009;Hsieh et al, 2003). In angioleiomyomas, as with the majority of benign tumors, features such as consumptive coagulopathy are not typically seen.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…It is exceedingly rare for this tumor to be found in a location other than the lower extremities. From 1966 to 2007, only 11 cases of uterine angioleiomyoma were reported in the current English literature (Cobellis et al, 2007;Culhaci et al, 2006;Hakverdi et al, 2009;Hsieh et al, 2003). In angioleiomyomas, as with the majority of benign tumors, features such as consumptive coagulopathy are not typically seen.…”
Section: Introductionmentioning
confidence: 91%
“…This type of leiomyoma is composed of smooth muscle cells and thick-walled vessels. It is frequently seen on the skin of the lower extremities in adults aged forty to sixty (Culhaci et al, 2006;Weiss and Goldblum, 2001). It is exceedingly rare for this tumor to be found in a location other than the lower extremities.…”
Section: Introductionmentioning
confidence: 95%
“…Since they are very uncommon, there is not enough information about the MRI appearance of retroperitoneal angioleiomyomas. However, previous reports in the literature about uterine angioleiomyomas (10,(13)(14)(15)(16) agree that these tumors show areas of cystic degeneration. Hsieh et al mentioned prominent tortuous vascular-like enhancing structures in uterine angioleiomyomas on CT examination (14).…”
Section: Discussionmentioning
confidence: 91%
“…Angioleiomyoma usually occurs in the subcutaneous tissue, most often in the lower extremities (1). It can very rarely be located in the head and neck region (11), in the submandibular gland (12), or in the uterus (10,(13)(14)(15)(16). There are only a few cases of retroperitoneal angioleiomyoma reported in the literature (2-4).…”
Section: Discussionmentioning
confidence: 99%
“…A comprehensive literature review showed that ALM is rarely located in the female genital tract. Only a few cases reports of uterine ALM have been described [2] ; however, ALM arising from the ovary has not yet been reported. As in our case, preoperative diagnosis may be difficult.…”
Section: Resultsmentioning
confidence: 99%